2007
DOI: 10.1074/mcp.m600275-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Ring1B/Rnf2 Interactors Identifies a Novel Complex with the Fbxl10/Jhdm1B Histone Demethylase and the Bcl6 Interacting Corepressor

Abstract: Ring1B/Rnf2 is a RING finger protein member of the Polycomb group (PcG) of proteins, which form chromatinmodifying complexes essential for embryonic development and stem cell renewal and which are commonly deregulated in cancer. Ring1B/Rnf2 is a ubiquitin E3 ligase that catalyzes the monoubiquitylation of the histone H2A, one of the histone modifications needed for the transcriptional repression activity of the PcG of proteins. Ring1B/Rnf2 was shown to be part of two complexes, the PRC1 PcG complex and the E2F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(206 citation statements)
references
References 73 publications
8
192
2
2
Order By: Relevance
“…An intriguing alternative possibility is that BCL6 itself may bind this region and lead to reduction in H3K4me3. In this regard, it is interesting that BCOR, a BCL6 corepressor, associates with FBXL10, a H3K4me3 demethylase (32,33). The BCL6 promoter region and intron 1 contain seven conserved predicted BCL6 binding sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing alternative possibility is that BCL6 itself may bind this region and lead to reduction in H3K4me3. In this regard, it is interesting that BCOR, a BCL6 corepressor, associates with FBXL10, a H3K4me3 demethylase (32,33). The BCL6 promoter region and intron 1 contain seven conserved predicted BCL6 binding sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by demonstrated the interaction of the JmjC HDM JARID1d with the polycomb-like protein RING6a/ MBLR and showed that RING6a/MBLR enhanced JARD1d-mediated H3K4 demethylation, associated with transcriptional repression. Jhdm1b has also been shown to interact with PcG proteins in a complex containing Ring1b/Rnf2 and the Bcl6 interacting corepressor, among other proteins (Sanchez et al, 2007). This co-repressor complex may be implicated in gene repression mediated by Bcl6, a transcription factor frequently dysregulated in B-cell lymphomas, and could provide the basis for studying the effect of HDM inhibitors in this disease.…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…Fbxl10 was previously reported to confer specific changes in histone modification either directly via its JmjC domain or indirectly by its binding partners (10,12,23,24). Whereas H3K4me3 and H3K36me2 were discussed as direct targets, H3K27me3 and H2Aub were reported as indirect targets because Fbxl10 was found in Polycomb complexes with H3K27 methylation activity and H2A ubiquitination capability (23,24).…”
Section: Stable Overexpression Of Fbxl10 Leads To An Increase In Cellmentioning
confidence: 99%